DETERMINING THE GENERIC STRATEGIES OF BUSINESS COMPETITORS - K. Papazov, Emil; M. Mihaylova, Lyudmila (Horizons - International Scientific Journal, 2020)
Establishing the business strategies of competitors is an important prerequisite for developing company’s own strategic path. The focus of this paper is the so-called generic strategies, whereas two main approaches for clarifying their nature are discussed. The first one is based on individual product characteristics and the second one builds on achieved financial results. The advantages and disadvantages of these approaches and the related specific methods are commented in view of the possibilities for their usage in the strategic analysis of smaller businesses. Particular attention is paid to the “Profitability-Turnover(P-T)” matrix developed by the authors.